Acoustic Comparisons of Red Palm Weevil (Rhynchophorus ferrugineus) Mortality in Naturally Infested Date Palms after Injection with Entomopathogenic Fungi or Nematodes, Aluminum Phosphide Fumigation, or Insecticidal Spray Treatments - Koko D. Sutanto; Mureed Husain; Khawaja G. Rasool; Richard W. Mankin; Abdalsalam O. Omer; Abdulrahman S. Aldawood (Insects, 2023)
Red palm weevil (RPW) management is important to the economic success of date palm agriculture. Monitoring with acoustic sensors was conducted in naturally infested trees in date palm orchards for six months after treatments with entomopathogenic fungi (Beauveria bassiana and Metarhizium anisopliae), entomopathogenic nematodes (Steinernema carpocapsae), aluminum phosphide, emamectin benzoate, or fipronil to evaluate their efficacy in an integrated pest management treatment vs. a distilled water injection. Reductions in the mean rates of RPW sound impulse bursts over time after treatment were used as indicators of RPW mortality. Entomopathogenic fungi and nematodes, aluminum phosphide, and emamectin benzoate were the most effective treatments, reducing RPW impulse burst rates within 2–3-months to levels indicating absence of infestation. However, when applied as a spray, fipronil had only a minor effect. The results indicate that treatments utilizing entomopathogenic fungi or nematodes can beneficially manage RPW in palm orchards and can help to limit treatments that may induce insecticide resistance or cause human and environmental harm. Furthermore, the use of an acoustic sensor can be beneficial in monitoring the activities of insect borers inside the tree trunk.